Keberhasilan Pemimpin dalam Implementasi Manajemen Perubahan - Hazizah, Nur; Aslami, Nur (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
The driver of leadership success is the effort and cooperation of all organizational devices. And the influence of a decisive leader produces satisfactory success, because it is able to organize the course of a group to be more directed at the goals that have been set. Leaders carry the mandate to lead, while leadership is the talent and behavior that must be held by the leader. Leaders are also actors who influence and influence their adherents so that something that the group aspires to is achieved well. Changes that occur get positive and negative responses. The existence of a positive response is characterized by a willingness to change and adapt. While change gets a negative response if there is resistance to change. This usually happens when members of the organization are comfortable and do not benefit from the change. The change process refers to several aspects, the first aspect is the extent of member participation in making changes. The second aspect is implementation in change. The final aspect is the readiness of individual members to respond and accept change